If you give a mouse a brownie - Numeroff, Laura Joffe (If you give, 2016)
If you give a mouse a brownie, he's going to ask for some ice cream to go with it. When you give him the ice cream, he'll probably ask you for a spoon. He'll start drumming on the table. Drumming will get him so excited he ll want to start a band ...